Implementation of Sufi Psychology Toward Moral Disorientation In The Era of Disruption From The Quran Perspective - Zulki, Ahmad; Darwis, Rizal; Abdillah, Abdillah (Farabi, 2023)
This article aims to analyze the psychology of Sufis in the industrial era 4.0 from the perspective of the Koran. This research is library research using the tafsir maudhu'i method (based on theme in the Koran interpretation) which refers to the verses of the Koran. The results of the study show that Sufi psychology directs and guides the moral and spiritual decline of modern humans to become human beings with Qur'anic character in increasing productivity and creativity in the industrial era 4.0. Sufi psychology presents a path of balance between the body and the spirit. The Sufi psychology approach in responding to modern human life in the industrial era 4.0 is carried out by contextualizing the verses of the Koran based on Sufi psychology. Sufistic verses of the Qur'an in various terms, namely, al-taubah (repetance), al-sabr (patient), al-faqr (a situation where the heart does not need except to Allah), al-zuhud (the decision to forget the world to love Allah SWT alone), al-wara', al-tawakkal and al-rida, is used as a basis for guiding and directing dynamic and diverse developments and changes in the contemporary modern era 4.0. Sufi psychology also serves to revitalize moral and spiritual disorientation in the contemporary modern era.